1985
DOI: 10.1002/jlb.37.1.109
|View full text |Cite
|
Sign up to set email alerts
|

The Modification of the Oxidative Metabolism of Cells Derived Both Locally and at Distance From the Site of an Acute Inflammatory Reaction

Abstract: During an acute nonspecific inflammatory reaction initiated in the pleural cavity by a nondiffusible stimulus (calcium pyrophosphate crystals), the oxidative metabolism, as measured by chemiluminescence and superoxide release, of cells harvested from both the inflammatory site and at points distant from it was studied. The oxidative metabolism of peritoneal macrophages, obtained from rats undergoing an inflammatory reaction (pleurisy), demonstrated a transient decrease in activity compared with the resident po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1985
1985
2005
2005

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…This phenomenon did not seem to be related to release of endogenous corticosteroids since the same results were obtained with adrenalectomised animals. The decrease in CL response did not appear to be due to impaired binding and internalisation of zymosan because similar results [11] have been obtained using a soluble (Phorbol myristate acetate) stimulus suggesting the cells were metabolically less responsive. It must be emphasized that during this phenomenon the cell population in the peritoneal cavity was unchanged in terms of total number, gross morphology and staining characteristics for esterase and peroxidase.…”
Section: Discussionsupporting
confidence: 77%
“…This phenomenon did not seem to be related to release of endogenous corticosteroids since the same results were obtained with adrenalectomised animals. The decrease in CL response did not appear to be due to impaired binding and internalisation of zymosan because similar results [11] have been obtained using a soluble (Phorbol myristate acetate) stimulus suggesting the cells were metabolically less responsive. It must be emphasized that during this phenomenon the cell population in the peritoneal cavity was unchanged in terms of total number, gross morphology and staining characteristics for esterase and peroxidase.…”
Section: Discussionsupporting
confidence: 77%
“…Activation of resident macrophages would result in additional release of cytokines, spreading outward toward taste receptor cells. In fact, paracrine effects of macrophages have been shown at sites distant to the initial inflammation in vivo (Bird et al, 1985) and in vitro (Ko et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…73, No. 4,1990 was tested in parallel with the decrease in milk and a-lactalbumin production during mastitis, a significant negative correlation was obtained with both stimuli. From these results, it was concluded that: 1) a high phagocytic potency and 2 ) elevated blood neutrophil numbers in combination with a high ROS-producing competence limited bacterial replication in the mammary gland.…”
Section: Dlscusslonmentioning
confidence: 92%
“…73, No. 4,1990 and local antibiotic treatment: 1) after the morning milking polymyxin B (500,000 IU, PomesulB, Bayer, Brussels) was injected into inflamed quarters; and 2) trimethoprim (1 g) plus sulfadoxin (5 g) was injected twice a day i.v. (Duoprim@, Coopers Agrovet, Aalst, Belgium).…”
Section: Bacteriamentioning
confidence: 99%